Pemanfaatan Daun Kelor sebagai MP – ASI dalam Upaya Peningkatan Status Gizi Balita - Diah Atmarina Yuliani; Purwati Purwati; Isnaeni Rofiqoch (LPPM Akbid Harapan Ibu Pekalongan, 2021)
MP – ASI is a trantition process from mik to semi – solid food. MP – ASI should be introduced and given gradually in both form and amount, according to the child’s digestive ability. Breast feeding only meets the nutritional needs of infants as much as 60% of the needs of infants aged 6 -12 months. The rest must be met with other complementary foods that are sufficient in numbe and nutritious. Provide training to cadres of Ranting Aisyiyah Tanjung Purwokerto Selatan on MP – ASI. Follow up activities were carried out in the fourth month of activity with the resuluts of morning tha the cadre mothers understood the various kinds of making MP – ASI made from Moringa leaves. The importance of this community service is increasing knowledge of mothers about MP – ASI in general and the use of MP – ASI made from local Moringa leaves.